Nogo-B promotes epithelial-mesenchymal transition in lung fibrosis via PERK branch of the endoplasmic reticulum stress pathway - Zhu, Ying (Ann Transl Med, 2021)
BACKGROUND: Idiopathic pulmonary fibrosis (IPF) is a fatal chronic pulmonary fibrosis disease and pathological mechanisms of fibrogenesis in IPF are still to be elucidated. Here, we investigated the potential role of Nogo-B in pulmonary fibrogenesis. METHODS: A mouse model of pulmonary fibrosis was established by intratracheal injection of bleomycin (BLM). Lung epithelial cells MLE-12 and TC-1 JHU-1 were cultured for TGF-β treatment. The extent of lung fibrosis was evaluated using hematoxylin and eosin (HE) staining and Masson staining in model mice and Nogo-B knockout mice. The protein levels of Nogo-B, endoplasmic reticulum stress (ERS) sensors including PERK, IRE1α, ATF6 and epithelial-mesenchymal transition (EMT) markers including E-cadherin and N-cadherin, vimentin were assayed by Western blotting respectively after Nogo-B knockdown or overexpression with lentivirus. Enzyme-linked immunosorbent assay (ELISA) was used to evaluate cytokine levels of TGF-β, TNF-α, IL-1β, IL-6 and IL-10 in bronchoalveolar lavage fluid (BALF). RESULTS: Nogo-B expression was up-regulated in lung tissues of fibrosis model mice and alveolar epithelial cells. Nogo-B knockdown significantly attenuated lung fibrogenesis, downregulated the levels of inflammatory cytokines, inhibited EMT as well as decreased the level of phosphor-PERK/PERK but not the levels of phosphor-IRE1α/IRE1α and c-ATF6. Additionally, a potential efficacy of PERK blockade was demonstrated in improving the extent of lung fibrosis in model mice. CONCLUSIONS: This study discovered that involvement of Nogo-B in pulmonary fibrogenesis was associated with the PERK branch of ERS pathway and EMT. Nogo-B could be considered as a potential therapeutic target for the treatment of IPF.